COMPARATIVE STUDY BETWEEN SCAFFOLDING TECHNIQUE AND GUIDED WRITING TO IMPROVE STUDENTS’ WRITING ABILITY AT NINTH GRADE OF SMPN 5 TOLITOLI - Andriana Andriana (Universitas Madako Tolitoli, 2020)
The objective of this research was to find out the significant difference between scaffolding technique and guided writing improving students’ writing ability at the ninth grade of SMPN 5 Tolitoli. It was a true-experimental research. It was conducted at ninth grade of SMP Negeri 5 Tolitoli. The researcher gave a pre-test to measure the students’ previous ability in writing. After gave treatment scaffolding technique and guided writing, the researcher gave post-test to the students. In analyze the data collection the researcher use SPSS 21 program. Based on data analysis showed that, there was significant effect of scaffolding technique and guided writing in students’ writing ability. The mean score of post test in scaffolding technique (84,05) was higher than the mean score of pre-test (52,00). And the mean score of post-test in guided writing (86,60) was higher than the mean score of pre-test (52,05). Although, the improvement in guided writing was higher than scaffolding technique but the testing of hypothesis showed that the value of tcount was lower than ttable (-0,755≤2.024). Hence, there was no a significance difference of students’ achievement score between who were thought scaffolding technique and guided writing at ninth the grade of SMPN 5 Tolitoli.Keywords: Comparative, scaffolding technique, guided writing, writing ability.